A minimally invasive technique for decompression of Chiari malformation type I (DECMI study): study protocol for a randomised controlled trial. Issue 4 (29th April 2015) - Hu, Yu; Liu, Jiagang; Chen, Haifeng; Jiang, Shu; Li, Qiang; Fang, Yuan; Gong, Shuhui; Wang, Yuelong; Huang, Siqing
Abstract : Introduction: Chiari malformation type I (CM-I) is a congenital hindbrain anomaly that requires surgical decompression in symptomatic patients. Posterior fossa decompression with duraplasty (PFDD) has been widely practiced in Chiari decompression, but dural opening carries a high risk of surgical complications. A minimally invasive technique, dural splitting decompression (DSD), preserves the inner layer of the dura without dural opening and duraplasty, potentially reducing surgical complications, length of operative time and hospital stay, and cost. If DSD is non-inferior to PFDD in terms of clinical improvement, DSD could be an alternative treatment modality for CM-I. So far, no randomised study of surgical treatment of CM-I has been reported. This study aims to evaluate if DSD is an effective, safe and cost-saving treatment modality for adult CM-I patients, and may provide evidence for using the minimally invasive procedure extensively. Methods and analysis: DECMI is a randomised controlled, single-masked, non-inferiority, single centre clinical trial. Participants meeting the criteria will be randomised to the DSD group and the PFDD group in a 1:1 ratio. The primary outcome is the rate of clinical improvement, which is defined as the complete resolution or partial improvement of the presenting symptoms/signs. The secondary outcomes consist of the incidence of syrinx reduction, postoperative morbidity rates, reoperation rate, quality of life (QoL) and healthcare resource utilisation. A total of 160 patients will be included and followed up at 3 and 12 months postoperatively. Ethics and dissemination: The study protocol was approved by the Biological and Medical Ethics Committee of West China Hospital. The findings of this trial will be published in a peer-reviewed scientific journal and presented at scientific conferences. Trial registration number: ChiCTR-TRC-14004099.